Sensitivity of maize to herbicides in experiments in Martonvásár in 2015 - Bónis, Péter; Árendás, Tamás; Szőke, Csaba; Sugár, Eszter; Fodor, Nándor; Darkó, Éva; Marton, Lajos (Acta Agraria Debreceniensis, 2015)
The phytotoxic effect of herbicides applied post-emergence was investigated in a herbicide sensitivity experiment set up on parental maize genotypes in Martonvásár. A total of 48 Martonvásár inbred lines and 12 single line crosses were included in small-plot experiments set up in two replications. Ten herbicides were applied at the normal authorised rate and at twice this quantity. Compounds intended for pre-emergence application were applied when maize was in the 3–4-leaf stage and post-emergence herbicides in the 7–8-leaf stage of development. The extent of phytotoxicity was scored two weeks after treatment. Some of the herbicides tested are not authorised for use in seed production fields, but it is important to know how the parental genotypes respond to all types of herbicides. Phytotoxic symptoms of varying intensity were only observed on a third of the 60 parental genotypes examined; the majority of the lines exhibited no reaction to any of the herbicides. Averaged over the 60 genotypes the level of phytotoxic damage was less than 10% for the single dose. When the double dose was applied somewhat more severe damage was induced by products containing Mesotrione + Nicosulfuron or Foramsulfuron + Isoxadifen-ethyl, but this was still below 15%. The herbicide dose had a three times stronger influence on the intensity of the symptoms than the type of herbicide. With the exception of Topramezone, there was a significant difference between the effects of the normal and double doses. The greatest dose effect differences, in decreasing order, were observed for Mesotrione + Nicosulfuron, Foramsulfuron + Isoxadifen-ethyl. Nicosulfuron and Mesotrione + Terbutylazine. The Mesotrione + Terbutylazine active ingredient combination only caused mild (